Acacetin Induces Apoptosis in Human Osteosarcoma Cells by Modulation of ROS/JNK Activation - Wang S; Lin B; Liu W; Wei G; Li Z; Yu N; Xue X; Ji G (Dove Medical Press, 2020)
Shubin Wang, Binhui Lin, Wei Liu, Guojun Wei, Zongguang Li, Naichun Yu, Xiang Xue, Guangrong Ji Department of Orthopedic Surgery, Xiang’an Hospital of Xiamen University, Xiamen City, Fujian, People’s Republic of ChinaCorrespondence: Guangrong JiDepartment of Orthopedic Surgery, Xiang’an Hospital of Xiamen University, No. 2000, Xiang’an East Road, Xiang’an District, Xiamen City, Fujian Province 361000, People’s Republic of ChinaTel +86-13945107257Fax + 0954-2683908Email 15755188821@163.comPurpose: The long-term survival rate of osteosarcoma, which is the most common type of primary malignant bone tumor, has stagnated in past decades. Acacetin is a natural flavonoid compound that has antioxidative and anti-inflammatory effects and exhibits extensive therapeutic effects on various cancers. In this study, the anticancer potential of acacetin and the underlying molecular mechanisms were examined in human osteosarcoma cells (SJSA and HOS).Materials and Methods: HOS and SJSA cell lines were exposed to different concentrations of acacetin. Cell proliferation and viability were assessed by CCK-8 and colony-formation assays. Hoechst 33258 fluorescent staining was employed to detect apoptosis. Cell apoptosis was measured by an annexin V-FITC/PI assay by flow cytometry. The alteration in the mitochondrial membrane potential was detected by a JC-1 Assay Kit. Apoptosis-related protein expression was determined by Western blotting. Intracellular reactive oxygen species (ROS) production was detected by fluorescence microscopy and flow cytometry. Subsequently, the activation of the ROS/JNK signaling pathway was investigated.Results: Acacetin could inhibit proliferation and induce apoptosis in SJSA and HOS cells. The acacetin treatment resulted in the activation of caspase-3, − 8, and − 9 and cleaved PARP. Further studies showed that acacetin-induced apoptosis was attributed to ROS. In addition, we found that acacetin induced the activation of the downstream c-Jun N-terminal kinase (JNK) signaling pathway. Subsequently, after treatment with the ROS scavenger GSH and the JNK inhibitor SP600125, the apoptosis-inducing effect triggered by acacetin was significantly attenuated.Conclusion: The results of the present study indicate that acacetin may induce apoptosis to inhibit cell growth by activating the ROS/JNK signaling pathway in SJSA and HOS cells, suggesting that acacetin may be a promising candidate for the management of osteosarcomas.Keywords: acacetin, osteosarcoma, apoptosis, ROS/JNK activation